The improved electrochemical performance of cross-linked 3D graphene nanoribbon monolith electrodes1. Issue 15 (21st April 2015) - Vineesh, Thazhe Veettil; Alwarappan, Subbiah; Narayanan, Tharangattu N.
<x xml:space="preserve">Abstract</x> A novel 3D electrode using graphene nanoribbons (GNRs) is constructed using chemical cross-linking of 2D GNRs. The 3D electrode developed in this work outperformed its 2D counterpart in all the electrochemical reactions.